A Linguistic Landscape Analysis of Pannon Egyetem Utca. 12. Through a Multilingual Lens. - Rawshdeh, Ibrahim; Saed, Hala (Center of Language and Cultural Studies [CLCS], 2022)
The current study examines the linguistic landscape of one of the main streets of Veszprem, the street of Pannonia University (Egyetem Utca. 12). The importance of analyzing public signs and the distribution of languages on this street stems from its dynamic location. Pannonia University is an interesting enough reason to investigate the street. Its location is hypothesized to have an impact on the street's multilingual nature, especially since the existence of a student dormitory on the street attracts international students with different linguistic and cultural backgrounds. This investigation is based on a corpus of 53 images that will be analyzed according to the function of signs as well as the taxonomy of types of the multilingual information arrangement provided by Reh (2004), namely: duplicating, fragmentary, overlapping, and complementary. The present results indicate a strong presence and dominance of the local language (Hungarian) in the linguistic landscape of the university street in Veszprem, in comparison to a minor bilingual representation on signs. The linguistic landscape in Egyetem Utca. 12. doesn’t reflect the linguistic background of the speech community, regardless of the other spoken languages and the conditions of the city itself, which receives a significant number of international students and tourists who speak different languages and use English or German as a means of communication.